Nanopore Sequencing Provides Rapid and Reliable Insight Into Microbial Profiles of Intensive Care Units - de Siqueira, Guilherme Marcelino Viana; Pereira-dos-Santos, Felipe Marcelo; Silva-Rocha, Rafael; Guazzaroni, María-Eugenia (Frontiers in Public Health, 2021)
Fast and accurate identification of pathogens is an essential task in healthcare settings. Next generation sequencing platforms such as Illumina have greatly expanded the capacity with which different organisms can be detected in hospital samples, and third-generation nanopore-driven sequencing devices such as Oxford Nanopore’s minION have recently emerged as ideal sequencing platforms for routine healthcare surveillance due to their long-read capacity and high portability. Despite its great potential, protocols and analysis pipelines for nanopore sequencing are still being extensively validated. In this work, we assess the ability of nanopore sequencing to provide reliable community profiles based on 16S rRNA sequencing in comparison to traditional Illumina platforms using samples collected from Intensive Care Units from a hospital in Brazil. While our results point that lower throughputs may be a shortcoming of the method in more complex samples, we show that the use of single-use Flongle flowcells in nanopore sequencing runs can provide insightful information on the community composition in healthcare settings.